Subalternitas Penganut Ahmadiyah dalam Novel Maryam Karya Okky Madasari - Kumaniren, Fabiola Agusta Wassy (Tuturlogi: Journal of Southeast Asian Communication, 2022)
The issuance of the Indonesian Ulema Council (Indonesia: Majelis Ulama Indonesia or  MUI) fatwa declaring Ahmadiyya as a deviant sect and its followers as having departed from  Islamic teachings has impacted the stereotypes surrounding the majority community. The novel  "Maryam" is a work of fiction based on the experiences of Okky Madasari's best friend as an  Ahmadiyya adherents. The novel narrates the discrimination and injustice faced by Ahmadiyya  adherents and serves as a form of social criticism by the author towards the subaltern discourse  surrounding Ahmadiyya adherents. This research aims to identify the various forms of  subalternity experienced by Ahmadiyya adherents in the novel "Maryam". The research  specifically examines the different forms of subalternity imposed by the majority group against  Ahmadiyya adherents based on the concept of subalternity, which refers to the oppressed who  lack access to voice their concerns developed by Spivak. The utilization of critical discourse  analysis in this research helps identify and categorize the various forms of subalternity through  the predetermined data corpus. The compiled data corpus is the primary source for the  researcher to describe, interpret, and analyze the text, context, and discourse in the novel  "Maryam". The data corpus will be analyzed through three stages: 1. Description, 2.  Interpretation, and 3. Explanation. The research results indicate that the forms of subalternity  depicted by the author in the novel "Maryam" include marginalization and silencing.